2013
DOI: 10.1002/oby.20149
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue assessed by cardiac magnetic resonance imaging in patients with heart failure due to dilated cardiomyopathy

Abstract: Objective: We sought to investigate the association of the EAT with CMR parameters of ventricular remodelling and left ventricular (LV) dysfunction in patients with non-ischemic dilated cardiomyopathy (DCM). Design and Methods: One hundred and fifty subjects (112 consecutive patients with DCM and 48 healthy controls) underwent CMR examination. Function, volumes, dimensions, the LV remodelling index (LVRI), the presence of late gadolinium enhancement (LGE) and the amount of EAT were assessed. Results: Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 42 publications
3
42
1
6
Order By: Relevance
“…Altun et al 33 also reported that epicardial adipose tissue thickness was correlated with the angiographic severity of acute coronary syndrome. However, Doesch et al 35 stated that the amount of epicardial adipose tissue is decreased compared to healthy controls in patients with heart failure due to dilated cardiomyopathy, irrespective of LV function impairment, and also, increased epicardial adipose tissue as assessed by cardiac magnetic resonance imaging is associated with LV mass and volume in these patients. Recent reports has shown that the epicardial adipose tissue volume was highly associated with atrial fibrillation, even after adjustment for risk factors, including left atrial dilatation and BMI 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altun et al 33 also reported that epicardial adipose tissue thickness was correlated with the angiographic severity of acute coronary syndrome. However, Doesch et al 35 stated that the amount of epicardial adipose tissue is decreased compared to healthy controls in patients with heart failure due to dilated cardiomyopathy, irrespective of LV function impairment, and also, increased epicardial adipose tissue as assessed by cardiac magnetic resonance imaging is associated with LV mass and volume in these patients. Recent reports has shown that the epicardial adipose tissue volume was highly associated with atrial fibrillation, even after adjustment for risk factors, including left atrial dilatation and BMI 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis has been identified as an inflammatory disease, 30 and it has been shown that epicardial adipose tissue is associated with 3,31-33 but not specific to atherosclerosis, as the recent literature suggests that it is also higher in patients with atrial fibrillation, heart failure, and hypertension. [34][35][36] Bachar et al 32 showed that asymptomatic patients with coronary artery disease (CAD) have significantly more epicardial adipose tissue than patients without CAD.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Epicardial fat was manually delineated on end-diastolic short-axis slices, working from the most basal slice towards the most apical slice (Figure 1). 18,19 The mitral valve annulus position was used to differentiate between atrial and ventricular epicardial fat. Epicardial fat volumes were calculated by summation of epicardial fat volume of each slice using the modified Simpson's rule.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, in the large‐scale clinical trials of rosuvastain in chronic heart failure, patients with HFpEF were poorly represented, either because they were excluded from participation or were not recruited; these trials focused on patients with impaired systolic function. However, patients with HFrEF exhibit evidence of decreased epicardial fat, which typically provides a nourishing function in these individuals . By contrast, in patients with HFpEF, epicardial adipose volume is increased and is a source of inflammation and injury to the underlying ventricular muscle .…”
Section: Differential Effects Of Statins In Preserved Vs Reduced Ejementioning
confidence: 99%